Unpaid work and time use in Argentina at the beginning of the 21st century - Delfino, Andrea; Herzfeld, Claudia; Arrillaga, Hugo (Sociedad y Economía, 2018)
This paper presents and analyzes the main trends emerged from the “Survey on unpaid work and use of time” carried out for the first time in Argentina on last quarter of 2013, as a module of Annual Survey of Urban Homes. The survey collected responses from 65,000 individuals over 18 years-old, in villages of two thousand or more inhabitants throughout the country, which represents 80% of the whole Argentine territory. The trends that are analyzed correspond to the data related to two types of unpaid work: on the one hand, the household chores (housework) and the care of family members (children, sick or elderly care activities, and school support and/ or learning activities); and on the other, voluntary work (unpaid activities, freely done for the benefit of people outside the family).